Optimization of the Payment Process at Toko Pertanian Kurnia Manokwari Using Business Process Reengineering and Throughput Efficiency - Faizal Qadri Trianto; Suharso, Wildan (Primakara University, 2026)
Rapid advances in digital technology within the agribusiness sector require Micro, Small, and Medium Enterprises (MSMEs) to adapt their operational strategies to remain competitive. This study presents a single-case study conducted at Toko Pertanian Kurnia Manokwari, an agribusiness MSME in West Papua, which experiences inefficiencies in its payment and order fulfillment processes due to reliance on manual bank transfers and centralized owner-based verification. The study aims to optimize the payment process through the application of Business Process Reengineering (BPR) by modeling the existing (As-Is) and redesigned (To-Be) processes using Business Process Model and Notation (BPMN) and evaluating process performance with the ASME Standard Process Chart through throughput efficiency measurement. The analysis identifies centralized verification as a single point of failure that prolongs transaction cycle times. The proposed solution integrates an API-based automated payment gateway to replace manual verification. The results indicate that the As-Is process achieves a throughput efficiency of 35.48% with a total cycle time of 186 minutes, whereas the evaluation of the redesigned To-Be process model indicates a potential increase in throughput efficiency to 100% and a reduction in cycle time to 23 minutes. These findings demonstrate that BPR supported by digital payment system integration, based on To-Be process modeling, can significantly improve transaction efficiency and operational scalability in agribusiness MSMEs.